Disgust, politics, and responses to threat. Issue 3 (27th June 2014) - Inbar, Yoel; Pizarro, David
Abstract We address two questions regarding the relationship between political ideology and responses to threatening or aversive stimuli. The first concerns the reason for the connection between disgust and specific political and moral attitudes; the second concerns the observation that some responses to threat (i.e., neuroticism/anxiety) are associated with a more left-wing political orientation.